2018
DOI: 10.1111/rda.13361
|View full text |Cite
|
Sign up to set email alerts
|

Crocin supplementation during oocyte maturation enhances antioxidant defence and subsequent cleavage rate

Abstract: Contents The purpose of the present study was to assess the effect of crocin supplementation during oocyte maturation on the antioxidant defence and anti‐apoptotic ability and subsequent developmental competence of porcine oocytes. Oocytes were cultured in media containing 0, 300, 400 or 500 µg/ml of crocin. Upon maturation, the maturation rates, reactive oxygen species (ROS) and glutathione (GSH) levels, mRNA expression of genes (SOD, CAT, GPx, Bcl‐2, BAX and Caspase3), expression of cleaved caspase3 and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In pigs, it has been reported that supplementation with different antioxidants, such as crocin 26 , sphingosine-1-phosphate 27 or melatonin 28 , during in vitro maturation culture improved the cleavage rates. Nevertheless, when supplementation was performed exclusively during embryo culture, the cleavage rate was not affected 9 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, it has been reported that supplementation with different antioxidants, such as crocin 26 , sphingosine-1-phosphate 27 or melatonin 28 , during in vitro maturation culture improved the cleavage rates. Nevertheless, when supplementation was performed exclusively during embryo culture, the cleavage rate was not affected 9 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It has many biological and therapeutic activities, as it can act as an antioxidant, inflammatory, immunomodulatory agent, in addition to its ability to control cell proliferation and autoimmune diseases (Alaluf et al, 2002;Naess et al, 2007;Mostafavinia et al, 2016;Gholamnezhad et al, 2013). Recently, Chen et al (2019) evaluated the effect of crocin addition into maturation medium during porcine IVM and IVF. Supplementation with 400-500 µg/mL crocin during oocyte maturation increased the maturation rate (86.8% vs. 72.8%), cleavage rate (62.50% vs. 53.33%), glutathione (GSH) levels, and the transcription of antioxidant-related genes such as superoxide dismutase (SOD), catalase (CAT), and glutation peroxidase (GPx).…”
Section: Carotene Derivativesmentioning
confidence: 99%
“…In IVM studies with oocytes, the compounds, with antioxidant potentials, are the most explored because of the desire to supplement the in vitro culture media to reduce the oxidative stress (Santos et al, 2018). Therefore, several bioguided studies have been developed over the years to reduce the negative effects caused by oxidative stress, thus increasing efficiency and productivity, linked to the technique ( Table 1) Another characteristic, found in the bioguided studies with antioxidants in IVM, would be the investigation of the most abundant antioxidant molecules present in the extracts and oils (Nie et al, 2020;Chen et al, 2019;Mesalam et al, 2017). In all the works, the studied molecules were the most abundant components of their plant extracts and all yielded positive results, by increasing the rates of IVM and embryonic development in addition to decreasing cell apoptosis in different species.…”
Section: Types Of Bioactives and Their Applications In Oocyte Ivmmentioning
confidence: 99%